Mampukah Pemahaman Internet Memoderasi Persepsi Kemudahan, Keamanan dan Kerahasiaan Terhadap Minat Penggunaan E-Filing? - Lestari, Candra Dewi; Oktaviani, Rachmawati Meita (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p17, 2022)
The sampling technique used purposive sampling with the number of samples taken by 150 respondents. The data analysis technique used is multiple linear regression. Based on the results of the analysis carried out, it was found that perceived ease had no significant effect on interest in using e-filing, security and confidentiality had a positive and significant effect on interest in using e-filing, understanding of the internet had a significant effect on interest in using e-filing, understanding of the internet was not able to moderate perceived ease of interest in using e-filing. Understanding the internet is able to moderate the security and confidentiality of the interest in using e-filling. Keywords: Perception Of Ease; Security and Confidentiality; Understanding The Internet; Interest In Using E-Filling.